Fatigue resistance of all-ceramic fixed partial dentures – Fatigue tests and finite element analysis. Issue 3 (March 2018) - Heintze, S.D.; Monreal, D.; Reinhardt, M.; Eser, A.; Peschke, A.; Reinshagen, J.; Rousson, V.
Abstract: Objective: To estimate the fatigue resistance of a new translucent zirconia material in comparison to lithium disilicate for 3-unit fixed partial dentures (FPDs). Methods: Eighteen 3-unit FPDs (replacement of first upper molar) with a connector size of 4 mm × 4 mm were dry milled with a five-axis milling machine (Zenotec Select, Wieland, Germany) using discs made of a new translucent zirconia material (IPS e.max ZirCAD MT, Ivoclar Vivadent). Another 9 FPDs with a reduced connector size (3 mm × 4 mm) were milled. The zirconia FPDs were sintered at 1500 °C. For a comparison, 9 FPDs were made of IPS e.max Press, using the same dimensions. These IPS e.max Press FPDs were ground from a wax disc (Wieland), invested and pressed at 920 °C. All FPDs were glazed twice. The FPDs were adhesively luted to PMMA dies with Multilink Automix. Dynamic cyclic loading was carried out on the molar pontic using Dyna-Mess testing machines (Stolberg, Germany) with 2 × 10 6 cycles at 2 Hz in water (37 °C). Two specimens per group and load were subjected to decreasing load levels (at least 4) until the two specimens no longer showed any failures. Another third specimen was subjected to this load to confirm the result. All the specimens were evaluated under a stereo microscope (20× magnification). The number of cycles reached before observing a failure, and their dependence on the load and on the material, were modeled, using a Weibull model. This made it possible to estimate the fatigue resistance as the maximum load for which one would observe less than 1% failure after 2 × 10 6 cycles. In addition to the experimental study, Finite Element Modeling (FEM) simulations were conducted to predict the force to failure for IPS e.max ZirCAD MT and IPS e.max Press with a reduced cross-section of the connectors. Results: The failure mode of the zirconia FPDs was mostly the fracture of the distal connector, whereas the failure mode of the lithium disilicate FPDs observed to be the fracture of the connectors or multiple cracks of the pontic. The fatigue resistance with 1% fracture probability was estimated to be 488 N for the IPS e.max ZirCAD MT FPDs (453 N for repeated test), 365 N for IPS e.max ZirCAD MT FPDs with reduced connector size and 286 N for the e.max Press FPDs. All three IPS e.max ZirCAD groups statistically performed significantly better than IPS e.max Press ( p < 0.001). On the other hand, no significant difference could be established between the two IPS e.max ZirCAD MT3 groups with a 4 mm × 4 mm connector size ( p > 0.05). The allowable maximum principal stress ( σ max ) which did not lead to failure during fatigue testing for IPS e.max ZirCAD MT3 was calculated between 208 MPa and 223 MPa for FPDs with 4 mm × 4 mm connectors for 2 × 10 6 cycles. This value could also be verified for the FPDs of the same material with 3 mm × 4 mm connectors. On the other hand fatigue strength in terms of σ max at 2 × 10 6 cycles of IPS e.max Press was calculated to be between 78 and 90 MPa. Significance: The fatigue resistance of the translucent zirconia 3-unit FPDs was about 60–70% higher than that of the lithium disilicate 3-unit FPDs, which may justify their use for molar replacements, provided that a minimal connector size of 4 mm × 4 mm is observed. Even with a limited number of specimens ( n = 9) per group it was possible to statistically differentiate between the tested groups.